Kedudukan Hak Ulayat Masyarakat Hukum Adat Untuk Kepentingan Investasi - Talahatu, Roleine Marshin; Laturette, Adonia Ivonne; Radjawane, Pieter (BAMETI Customary Law Review, 2024)
Recognition of the customary customary rights of indigenous peoples has been recognised in the 1945 Constitution of the Republic of Indonesia, thus it is not explicitly mentioned in the PA Lawon customary rights or lordship rights, but nevertheless itrecognizes and respects the position of customary rights or lordship rights or the implementation of its management for investment purposes derived from state land and customary land are regulated in government regulations which are the implementation of the Job Creation Law, but in reality still cause disputes and / or conflicts antara mcommunity hukum adat with Investors related to Investment, this is the author's concern to study it in writing this thesis. The research method used in writing this thesis uses the normative juridical method. The results of the study found that, the position of customary rights is not state land but customary rights are a right to land that is different from other land rights, so that the arrangement and management for investment interests derived from customary rights to obtain customary law community land to carry out their business activities must not cause problems to local customary law communities so that the determination of customary rights into management rights is a form of state recognition of the customary rights of indigenous peoples. The purpose of the government regulation on management rights is to make it easier for investors to get land to invest because with the availability of land, investors can manage land to run their business, but in reality the management rights of land derived from customary rights of customary law communities for investment by entrepreneurs or companies still cause problems for local customary law communities. Given that the position of customary rights of customary law communities in reality still exists, related to its management derived from customary rights or customary land, customary law communities are expected to the government to the existence of customary rights or customary land, besides that there is also a need for the involvement of indigenous peoples in the implementation of investment activities and for the smooth implementation of investment activities, the Central Government and local governments may grant permits to investors to operate in the area where the investment object is located but there is also a need for the involvement of Customary Law Peoples through contracts or agreements with investors that must be carried out.